Fluid flow and heat transfer of nanofluids in microchannel heat sink with V-type inlet/outlet arrangement - Abdollahi, A. (Elsevier B.V., 2017)
The fluid flow and heat transfer characteristics of laminar nanofluid flow in microchannel heat sink (MCHS) with V-Type inlet/outlet arrangement are numerically studied. A constant heat flux boundary condition is applied on the base plate of MCHS and all the other surfaces of MCHS are insulated. Four different kinds of nanofluids are utilized as working fluids which are SiO2, Al2O3, ZnO and CuO dispersed in pure water as a base fluid. Three different volume fractions of 1%, 1.5% and 2% and three distinctive nanoparticle diameters of 30 nm, 40 nm and 60 nm were employed. The results specify that the SiO2 nanofluid has the uppermost heat transfer rate compared to other tested nanofluids. Increasing the nanoparticles volume fraction together with decreasing the nanoparticles diameter enhances the Nusselt number value. The pressure drop coefficient did not change significantly by using nanofluid with various volume fractions and varied nanoparticle diameters. Moreover, the results indicate that nanofluid can enhance the performance of MCHS with V-shaped inlet/outlet arrangement.